Prácticas familiares y desarrollo socioeducativo de los estudiantes de Educación Básica Preparatoria de la Unidad Educativa Sicalpa durante el año lectivo 2023-2024. - Vallejo Mendoza, Monica Alexandra (2024)
The purpose of this investigative work was to evaluate family practices in the socio-educational development of the students of Basic Preparatory Education of the Sicalpa Educational Unit. A quanlitative approach and a non-experimental design were used due to the exploratory scope, of a diagnostic type. The population consisted of 30 parents of preparatory Basic Education. The survey was used as a technique and a structured questionnaire as an instrument. Among the most relevant results, it was found that most parents used to talk about the future with their 5-year-old children, although a small percentage still did so sporadically. Expectations regarding the future were varied, with higher education being the most common choice, followed by a small group opting for a baccalaureate and work activities in the commercial field. Regarding practices related to socio-educational development at home, a weakening of teamwork and industriousness was identified, which indicated the need for continuous intervention. In conclusion, in most of the families surveyed, positive practices were observed that favored child maturity. However, areas of weakness were identified that should be considered in training programs for families.